19 Reduced Accuracy of GEM 4000 for Measurement of Electrolytes, Glucose, and Hemoglobin in Relation to Calibration Schedule. (11th January 2018) - Kattar, Mireille; Xu, Qian; Cembrowski, Adam; Mei, Junyi; Sadrzadeh, Hossein; Cembrowski, George
Abstract: Objectives: The GEM 4000 (Instrumentation Laboratory, Bedford, MA) is a point-of-care analyzer, primarily used in a critical care setting to measure blood gases, glucose, electrolytes, and hemoglobin. Previous studies have shown that the instrument demonstrates increased imprecision compared to similar analyzers for iCa, electrolytes, and blood gases when external quality control material is run. In this study, accuracy was assessed by comparing patient GEM test results to corresponding central laboratory results for patients whose point-of-care and central laboratory specimens were tested within 30 minutes of each other. Methods: A laboratory database was mined for measurements of glucose, electrolytes, and hemoglobin using two GEM 4000 instruments on intensive care unit patients at the Foothills Hospital in Calgary, Alberta, over a 2-year period (2012–2013). Results were compared to concurrent testing (≤30 minutes interval) performed using comparable central laboratory methods, the Roche Cobas 8000 for chemistry and Sysmex XN-3000 for hemoglobin. The mean absolute differences were calculated for each sequence of 1000 pairs of central laboratory and GEM results, and graphed against time of day. Results: The GEM displayed optimal accuracy in the early morning, coincident with the daily (2:00 am) analysis of calibrator solution (PSC C), and worsened, reaching peak inaccuracy and plateauing at 6–8 hours post-calibration. The analytes most affected were glucose, Na, K, and hemoglobin. The analytical variation of the GEM approached the corresponding biological variation (low sigma) for glucose, hemoglobin, and electrolytes except K. Conclusion: This data confirm the reduced accuracy of the GEM 4000 in nonmorning hours, which probably negatively impacts patient care, and calls for technological enhancements in the next-generation GEM instruments. Laboratories that use the GEM system should begin dialogues with its primary clinical users.